Otologic manifestations of Larsen syndrome. (October 2017) - Marques, Letícia Helena de Sousa; Martins, Daniela Vieira; Juares, Gabriel Liria; Lorenzetti, Fábio Tadeu Moura; Monsanto, Rafael da Costa
Abstract: Objective: To describe and discuss otologic manifestations of Larsen syndrome, based on a case report and a systematic review of the literature. Materials and methods: We performed a PubMED database search, and we selected studies reporting otolaryngologic manifestations secondary to Larsen syndrome. The selected articles were read in full, and three researchers independently extracted data from the studies. In parallel, we report the case of a 14-year-old patient who had hearing loss secondary to Larsen syndrome. Results: Fifteen studies met our selection criteria. Seven studies reported hearing loss in patients with Larsen syndrome (4 had conductive hearing loss and 3 had mixed hearing loss). The conductive hearing loss may be secondary to ossicular malformations and/or middle ear effusions. Other causes for conductive hearing loss are mesenchymal remnants in the middle ear, Eustachian tube dysfunction, and cleft palate. Surgical management of the hearing loss is possible in selected cases, although the surgical and anesthetic risks should be considered. Hearing aids seem to be safe and effective treatment options for the hearing loss secondary to Larsen syndrome. Conclusion: Although rare, patients with Larsen syndrome may have hearing loss. The most frequent type of deficit is conductive, either secondary to malformation of the ossicles or middle ear effusion. Possible surgical correction of these abnormalities should be weighed against the anesthetic risks of these patients.